PKM Pendampingan Usaha Mahasantri Dalam Berwirausaha Di Pondok Pesantren Nurul Jadid Paiton probolinggo - Nadhiroh, Anis; Aisyah, Siti Aisyah A; Risqiyatul, Risqiyatul hasanah; Ilmiyah, U’tiyatul I; Afita, Diah Afita K (Lembaga Dongan Dosen, 2023)
Unemployment rate among educated graduates is to foster interest in entrepreneurship as early as possible. This interest in entrepreneurship can be fostered through entrepreneurship education. Entrepreneurship education must be specifically designed to facilitate entrepreneurial learning at a young age. Entrepreneurship is an art that can be learned and developed. The aim of this PKM is implemented by providing assistance in project-based entrepreneurship which is able to grow the entrepreneurial interest of Nurul Jadid University students. The methods used in community service are: in the form of primary data, namely student students using interview techniques and observation using a check list sheet. Secondary data was collected from the Entrepreneurship and Alumni Section of Santri Patriot Panji Pelopor Nurul Jadid University, by interviews with management officers and documentation studies. The method of business assistance to business groups is carried out with 2 (two) activity plans, namely 1. Mentoring in the classroom (campus) and 2. Mentoring at the place of business (Mahasantri Dormitory).